Applicability of the territorialization process as a strategy for the development of health promotion in Primary Care (Research, Society and Development, 2021)
The concepts of territory and territorialization are problematized, based on different conceptions, in order to dialogue with the attributions and challenges of Health Surveillance and, especially. The objective of the article is to analyze in the literature the importance and applicability of the territorialization process as a strategic for the development of health promotion in Primary Care. This is an integrative review of a qualitative approach carried out in July 2021, through the Virtual Health Library (VHL) databases. To formulate the research question, the PICo strategy was used. From the surveillance of the territory, it is necessary to carry out the planning of actions, promotions and prevention of vulnerabilities. Thus, territorialization is an instrument for organizing work processes and health practices. They provided minimal information on the systems used, contributing even if it was difficult to develop their role in the surveillance of the territory. Therefore, it is considered that the territorialization process must recognize the perceptions and living conditions in order to propose actions to promote health in the community.